Autochthonous lactic acid bacteria with probiotic aptitudes as starter cultures for fish-based products. (August 2017) - Speranza, Barbara; Racioppo, Angela; Beneduce, Luciano; Bevilacqua, Antonio; Sinigaglia, Milena; Corbo, Maria Rosaria
Abstract: This study focused on the selection of lactic starters with probiotic properties for the production of fermented fish-products by the use of a multivariate approach (Cluster Analysis and Principal Component Analysis). Seventy-five isolates were recovered from fish intestinal microbiota and characterized by evaluating phenotypical, technological and probiotic traits; the most promising isolates were molecularly identified and then used into fish fermented sausage production. Namely, data from technological characterization were modelled through Growth Index and used as input to run a preliminary selection. Thus, 15 promising strains were selected and subjected to probiotic characterization; considering the results from probiotic tests, 3 promising strains were finally chosen (11, 68 and 69), identified as members of the genus Lactobacillus and used for the validation at laboratory level through the assessment of their performances for the production of fermented fish sausages. The results were promising as the use of the selected strains reduced the fermentation time (2 days) ensuring a good microbiological quality of the final product. Highlights: A lactic starter with probiotic aptitudes was proposed for fermented fish-products. A simple step-by-step methodology was used to select 3 promising strains. Selected strains reduced the fermentation time and improved the product.